Tangible or Intangible Ways to Happiness? Consumption Related Values Among Adolescents - Debreceni, János (European Journal of Multidisciplinary Studies, 2018)
In recent years a large number of consumer studies focused on happiness, subjective well-being and satisfaction with life in relationship with material or experimental consumption. Most of the studies applied statistically reliable validated scales and measurements involving large numbers of respondents. There are only a few study that aimed to answer the meaning of happiness or satisfaction and their reflections in adolescents’ consumer behaviour at the present time. Due to the less represented academic literature in that area and the controversial results of our previous quantitative research on materialism we decided to conduct a qualitative research to investigate the meaning of happiness among adolescents in Hungary. Our non-representative sample consisted of students from 5 different high schools in 3 cities including Budapest. Respondents took part in in-depth interviews, peer interviews and worked in groups in associative experiments. According to our findings physical goods and material consumption contribute less to the individuals’ sense of happiness and interpersonal relationships are more appreciated. The teenagers of our sample showed signs of material emptiness, since possessing things were unimportant for them Family, stable personal relationships and safety were very significant among their values. Their consumer behaviour was influenced mostly by the need for gaining experiences rather than need for acquisition and possession of tangible goods.
Keywords: tangible or intangible ways to happiness, consumption related values among adolescents